THE ABUNDANCE AND SPATIAL DISTRIBUTION OF PLANKTON COMMUNITIES IN BANGGAI ISLANDS WATERS - Hikmah Thoha; Arief Rachman (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2013)
Banggai Islands waters are mixing area between Banda Sea and Makassar Sea, thus resulting in the existence of many unique marine ecosystems. This conditon might also lead to the occurrence of unique and specific plankton community in the oceanic ecosystem of Banggai Islands. This research was conducted in 26 June to 8 July using Baruna VIII research vessel. Phytoplankton and zooplankton samples were collected in 14 stations using Kitahara and NORPAC plankton net. The plankton data in this research was analyzed with Bray-Curtis Clustering Analysis (Single Link), linear regression and Pearson correlation matrix. The results showed that zooplankton abundance was highest at the strait between Liang and Labobo Island, while phytoplankton was found abundant at eastern Tinangkung Island. On the other hand, Mesamat Bay was found having very low abundance of zooplankton and phytoplankton, which probably related to low nutrient availability in the water column. Calanoids, cyclopoids, and oikopleurans were dominant taxa with widest spatial distribution and highest importance value in zooplankton community of Banggai Islands. Meanwhile Chaetoceros, Rhizosolenia and Thalassiothrix were the dominant genus with widest spatial distribution and highest importance value in phytoplankton community. The result of clustering analysis showed that there were three stations with unique plankton community, and was found very different from the planktonic community in other stations. It was interesting to note that bottom-up control by nutrient availabilty, and top-down control by predator-prey interaction, probably not the main factor responsible for the unique pattern of plankton community structure of Banggai Islands. Keywords: plankton community, Banggai islands waters, Bray-Curtis clustering analysis, biological indices.